The Omicron variant: a South African perspective - Schoub, Barry (Henry Stewart Talks, 2022)
Omicron, South Africa and the origins of Omicron, The fourth wave, Properties of Omicron, 5 SARS-CoV-2 variants of concern, Omicron mutation profile, Omicron spike protein, Omicron transmissibility, Reproduction (R) number, Omicron immune evasion, Clinical expression of SARS-CoV-2 variants, The spread of Omicron, Population immunity, Viral fitness, Viral evolution